2016
DOI: 10.1007/s11832-016-0798-5
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of developmental dysplasia of the hip within the UK: Refining the risk factors

Abstract: PurposeThe epidemiology and risk factors for developmental dysplasia of the hip (DDH) are still being refined. We investigated the local epidemiology of DDH in order to define incidence, identify risk factors, and refine our policy on selective ultrasound screening.MethodsWith a cohort study design, data were prospectively recorded on all live births in our region from January 1998 to December 2008. We compared data on babies treated for DDH with data for all other children. Crude odds ratios (ORs) were calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
94
2
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(118 citation statements)
references
References 21 publications
5
94
2
11
Order By: Relevance
“…According to literature, DDH incidence in newborns considerably varies with geographical location from lowest in Africans, to highest in Native Americans and Caucasian population. The global incidence can roughly be estimated to 0.1-6.6 cases per 1000 live births and is responsible for up to 30% of primary THAs in people up to 60 years of age [15][16][17][18][19]. Variations in incidence considering geographical location can be caused by epigenetic factors, consanguinity rates or study limitations, e.g., group size and diagnostic methods used.…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…According to literature, DDH incidence in newborns considerably varies with geographical location from lowest in Africans, to highest in Native Americans and Caucasian population. The global incidence can roughly be estimated to 0.1-6.6 cases per 1000 live births and is responsible for up to 30% of primary THAs in people up to 60 years of age [15][16][17][18][19]. Variations in incidence considering geographical location can be caused by epigenetic factors, consanguinity rates or study limitations, e.g., group size and diagnostic methods used.…”
Section: Epidemiologymentioning
confidence: 99%
“…Factors such as oligohydramnios [30], high birth weight (HBW) or primiparity [18], present an increased risk for DDH.…”
Section: Limited Fetal Mobilitymentioning
confidence: 99%
“…9 Conversely, cases identified early often resolve spontaneously a few weeks later. 10 There is evidence that screening after 3 months can increase the rate of surgery, 11 although others have found that delayed screening improves the results. 12,13 Conversely, Roovers et al 6 found evidence that earlier screenings led to better detection of abnormal hips.…”
Section: Introductionmentioning
confidence: 99%
“…1) diagnostizieren [3]. Die Analyse der Geschlechterverteilung bestätigte die bisher bekannte Verteilung zugunsten des weiblichen Geschlechts [3,4].…”
Section: Epidemiologie Und äTiologieunclassified